Dose a Bladder Volume of 200 mL Generate Greater Urethral Mobility at Valsalva Movement in Female Patients with Stress Urinary Incontinence? - Ning Xiao; Li Gao; Xiangxi Yao; Xiaohua Gao; Qi Tang; Gaoyu Pan; Kailu Wei; Huasheng Zhao; Jianfeng Wang (Clinical and Experimental Obstetrics & Gynecology)
Background: Failure to standardize bladder volume in the evaluation of stress urinary incontinence (SUI) may be a contributing factor to the controversy surrounding the diagnostic and prognostic efficacy of urodynamic studies (UDS) in female patients with SUI. This study was conducted to explore the effects of bladder volume on the urethral mobility in female patients with SUI under increased intra-abdominal pressure. Methods: This prospective study enrolled uncomplicated female patients with SUI admitted to the Second Affiliated Hospital of Guilin Medical University and Shaoyang Central Hospital, between January 2021 and January 2024. Relative bladder neck descent (BND), urethral inclination angle (UTA), urethral rotation angle (URA), and posterior urethrovesical angle (PUVA) were compared across different bladder volumes (100 mL, 200 mL, and 300 mL) at resting state or 90 cm H2O of intravesical pressure, generated by Valsava movement, using sonography videourodynamic studies (SVUDS). Analysis of variance (ANOVA) was used to compare numerical data of parameters with a normal distribution. Results: 62 patients were enrolled in this study. There was not a significant difference in UTA and PUVA among the various bladder volumes (100 mL, 200 mL, and 300 mL) at resting state (all p >0.05). However, higher BND (2.23 ± 0.73 cm), UTA (44.7 ± 17.1°), URA (29.4 ± 16.0°), and PUVA (148.7 ± 21.4°) were determined at a bladder volume of 200 mL with the Valsalva movement (VM) reaching 90 cm H2O of intravesical pressure, compared to 100 mL (1.89 ± 0.74 cm, 38.1 ± 17.9°, 23.0 ± 15.5°, and 139.3 ± 19.8°) and 300 mL (1.85 ± 0.74 cm, 37.6 ± 18.8°, 23.8 ± 13.5°, and 143.4 ± 20.8°) (all p <0.05), except for PUVA between 200 mL and 300 mL (p = 0.161). Conclusions: Higher values of BND, UTA, URA, and PUVA at a bladder volume of 200 mL in the Valsalva state of female patients with SUI, compared to 100 mL and 300 mL, suggest that capacity of 200 mL should be standardized for evaluating female SUI.